2020
DOI: 10.15295/bmij.v8i2.1480
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Agile Leadership With Biomimicry-Based Gray Wolf: Proposing a New Model

Abstract: Biomimicry is a modern interdisciplinary approach that motivates leaders by nature to use its applications. Leadership is not only a subject of study in biology but also in all social sciences. This research focuses on understanding the mechanism behind the coordinated behaviour observed in mobile animal groups in order to assess the impact of leadership models in biology and sociology on group behaviours. In this context, this study aims to reveal the common grounds and to establish bridges between agile lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Research indicates that these leaders have specific characteristics, and competencies demonstrated through their leadership practices within complex educational environments (Joiner and Josephs, 2007). Agile characteristics are organisational leadership characteristics that leaders and followers engage in together and include collaboration, self-awareness, proficiency, flexibility, an ability to change and quick thinking and action (Akkaya and Yazici, 2020). These protean characteristics represent the cognitive agility of leaders demonstrated through their ability to remain versatile, flexible and adaptable (Johnson and Kruse, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research indicates that these leaders have specific characteristics, and competencies demonstrated through their leadership practices within complex educational environments (Joiner and Josephs, 2007). Agile characteristics are organisational leadership characteristics that leaders and followers engage in together and include collaboration, self-awareness, proficiency, flexibility, an ability to change and quick thinking and action (Akkaya and Yazici, 2020). These protean characteristics represent the cognitive agility of leaders demonstrated through their ability to remain versatile, flexible and adaptable (Johnson and Kruse, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%